Consumer bankruptcy in Austria: An empirical analysis - Stefan Angel; Philipp Warum (Austrian Institute of Economic Research (WIFO), 2024)
Private bankruptcy offers over-indebted persons the possibility to obtain a discharge of debts under certain conditions. From 1995 to 2023, a total of about 215,000 private bankruptcy petitions were filed in Austria. The annual number of applications rose steadily until the end of the 2000s. Since then, major jumps in the number of cases have been observed, especially in connection with reforms and changes in the political framework, such as during the COVID-19 crisis. This paper analyses the determinants of personal bankruptcies in Austria since their introduction in 1995. The vast majority of studies on personal bankruptcies refer to the USA, while the situation in Austria has hardly been investigated. We aim to fill this gap by applying time series and panel econometric methods to Austrian consumer bankruptcy data. We examine their relationship with policy, macroeconomic and socio-demographic variables. Our results indicate relatively large effects of bankruptcy rules (i.e. the changing conditions for debt discharge) and private debt levels.
Keywords: D18; G51; K35; 330; consumer bankruptcy; Austria; debt counseling